Profil Morfologi dan Difraksi Arang Hasil Pirolisis Beberapa Jenis Kayu Lokal Provinsi Bengkulu, Indonesia: Morphology and Diffraction Study of Charcoal By-Products from the Pyrolysis of Several Local Woods from Bengkulu Province, Indonesia - Nurwidiyani, Ria; Triawan, Deni Agus; Rahman, Arief Aulia; Yudha, Sal Prima (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2024)
Wood, as a basic material for the furniture industry, creates waste problems in the form of wood sawdust. Wood sawdust is a material that can be utilized by processing it through a pyrolysis process to produce liquid smoke and charcoal. Charcoal resulting from sawdust pyrolysis of Azadirachta excelsa, Durio zibhetinus, Swietenia mahagoni, and Coffea sp. wood has different characteristics. Pyrolysis was carried out at 300–350 °C for 6 hours. Characterization was carried out using SEM-EDS and XRD. Based on the research, it is known that the character of the charcoal resulting from pyrolysis using XRD shows that the charcoal composition of each wood has similar characteristics, as indicated by the presence of a broad peak at 2 theta 25° indicating that the charcoal formed has an amorphous structure. In comparison, the 2 theta peaks of 17° and 29° respectively, indicate the presence of lignin and CaCO₃ in charcoal. The morphological structure of the charcoal surface based on the results of SEM analysis shows a similarity in morphology between Swietenia mahagoni and Coffea sp. Wood charcoal with small pore diameters and distances apart, as well as between Durio zibhetinus and Azadirachta excelsa wood charcoal, which resembles a honeycomb structure. The composition of charcoal resulting from pyrolysis shows that the largest component of charcoal is carbon with a percentage of 45.4-56%, calcium with a percentage of 10-15.2%, and oxygen with a percentage of 22.5-38.4%, with minor components in the form of aluminum, boron, silicon, and potassium.